Determinants of Prolonged Postoperative Length of Stay After Carotid Revascularization: A Single-Center Registry Analysis from Kazakhstan - Almas Shamshiyev; Shokan Kaniyev; Askar Matkerimov; Manat Zhakubayev; Talgat Demeuov; Mead Khanchi; Almas Saduakas; Rustam Makkamov; Nurlybek Yerkinbayev; Alisher Kozhamkul; Gulnaz Nurlybaeva; Mukhtar Kulimbet (Journal of Clinical Medicine, 2026)
Background/Objectives: Carotid revascularization reduces stroke risk in patients with carotid stenosis. Postoperative length of stay (LOS) reflects resource utilization and recovery, yet its determinants remain poorly described in Central Asia. This study examined whether baseline patient characteristics predict prolonged postoperative LOS in a Kazakhstani referral cohort. Methods: We analyzed a single-center retrospective cohort (clinical registry) of 320 consecutive patients who underwent carotid revascularization between January 2018 and December 2025. Carotid endarterectomy (CEA) was performed in 88 patients (27.5%) and carotid artery stenting (CAS) in 228 (71.2%). Prolonged postoperative LOS was defined a priori as >8 days (75th percentile). Multivariable logistic regression was performed, with negative binomial regression; a model additionally including procedure type, and a model including in-hospital complications were used as sensitivity analyses. Results: Patients were predominantly male (74.7%) with a mean age of 71.1 ± 7.5 years and a high burden of comorbidities. Median postoperative LOS was 6 days (IQR 4–8), and 72 patients (22.5%) had prolonged LOS. Postoperative LOS was similar after endarterectomy and stenting (median 6 vs 5 days). In-hospital complications occurred in 11 patients (3.4%), with two deaths (0.6%). No baseline characteristic independently predicted prolonged LOS (all p > 0.05; AUC = 0.629; Hosmer–Lemeshow p = 0.45), and procedure type was not associated with prolonged LOS (adjusted OR 1.14, 95% CI 0.61–2.14). In contrast, in-hospital complications were strongly associated with prolonged LOS (adjusted OR 8.50, 95% CI 2.04–35.40; p = 0.003), although this estimate was imprecise owing to the small number of events. Median postoperative LOS increased from 6 days in patients without complications to 12.5 days in those with complications (p < 0.001). Conclusions: In this elderly, comorbidity-heavy cohort, prolonged postoperative LOS was associated with perioperative complications rather than baseline patient characteristics. Because complications lie on the causal pathway between baseline risk and hospital stay, this finding is best interpreted as hypothesis-generating: it suggests that efforts to shorten stay may be better directed toward complication prevention than preoperative risk stratification, a hypothesis that warrants prospective evaluation.